Air pollution monitoring system using unmanned aerial vehicle in Bangladesh - Al-Farabi, Md.; Chowdhury, Muntasir; Hossain, Md. Rafat; Readuzzaman, Md. (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.